Socioeconomic inequalities in exposure to environmental tobacco smoke in children in Israel. (December 2018) - Berman, Tamar; Barnett-Itzhaki, Zohar; Axelrod, Rachel; Keinan-Boker, Lital; Shimony, Tal; Goldsmith, Rebecca; Göen, Thomas; Geva, Haim; Rosen, Laura
Abstract: Background: Environmental tobacco smoke (ETS) exposure in infants and children causes more frequent and severe asthma attacks, respiratory infections, ear infections, and sudden infant death syndrome. The aim of this study was to measure ETS exposure in children in Israel (ages 4–11 years) using urinary cotinine measurements, in order to compare exposure levels to other international populations, and to assess predictors of ETS exposure in children in Israel. Methods: A subset of children who participated in the National Health and Nutrition Survey (RAV- MABAT) in 2015–2016 were invited to participate in the Second Israel Biomonitoring Survey. We analyzed urinary cotinine and creatinine concentrations in 103 children. Parents of study participants were interviewed in person on children's exposure to ETS at home and in other environments and on sociodemographic variables. We calculated creatinine-adjusted and unadjusted urinary cotinine geometric means in children and analyzed associations in univariable and multivariable analyses, between sociodemographic variables and parental – reported exposure, and urinary cotinine concentrations. Results: Based on urinary creatinine measurement, over 60% of children are exposed to ETS (compared to <40% based on parental report). Linear regression showed a positive association between urinary cotinine concentration and reported ETS exposure (p = 0.001). Mean cotinine concentration among children whose parents reported that they are exposed to ETS at home (5.1 μg/l) was significantly higher than the concentration among children whose parents reported they are not exposed to ETS at home (1.6 μg/l, p < 0.001). There was an inverse relationship between total family income and urinary cotinine concentration (p < 0.05). In a multivariable model adjusted for ethnicity and other factors, family income was a significant predictor of urinary cotinine level (p = 0.04, slope = −0.49). Geometric mean creatinine adjusted concentrations in children in the current study were higher than in children in Canada and selected European countries. Conclusions: We found evidence of widespread exposure to ETS in children in the study. There is an urgent need to protect children in Israel from exposure to ETS. Highlights: We measured urinary cotinine in 103 children to assess ETS exposure in Israel. Over 60% of children were exposed to ETS compared to <40% based on parental report. Lower family income was found to predict higher cotinine concentrations in children. We found evidence of widespread exposure to ETS in children in the study.